Licenciamento ambiental, energia e desenvolvimento: caso da usina hidrelétrica Jirau - Souza, Arivaldo Santos de (2011)
This dissertation thesis examines the environmental licensing of a hydroelectric power plant in the Amazon Basin: 'Usina Jirau.' This starting point for this case study was an allegation that the Brazilian environmental licensing process for hydroelectric power plants slows down the Brazilian development. As an initial matter, I assumed that such an argument is partially mistaken. On the one hand there may be problems in the administrative procedures and in the institutional design and functioning of the environmental agency, IBAMA; but on the other hand, the entrepreneurs did not properly consider legal environmental rules during the planning process. To test this hypothesis, I attended specific meetings on the subject, conducted interviews with key actors in the process, and researched the issues raised in different courts by a variety of litigators. I also analyzed the environmental licensing procedures extensively and some other to understand the economic argument, its variations and the proponents of such ideas. Additionally, I explain how and which hypotheses were tested in my research. In part II, I discuss the environmental licensing economic content, put the environmental documents from both state and non-state players. This paper is divided into four separate parts, and a conclusion. In part I, I explain the research problem, the context surrounding the construction of Usina Jirau as well, discuss some key players, and demonstrate how licensing rules together, and assess how the two aforementioned perspectives relate to each other. In part III, I describe the IBAMA bureaucracy functions as a means of assessing if, as a public administration, it was inefficient in licensing Usina Jirau. Thus, I describe the IBAMA authority to license such entrepreneurship, its structure and ability to provide this service, and list other administrative branches and entrepreneurs’ obligations. Lastly, I identify what were the sensitive points in the environmental licensing dynamics, which may have offered obstacles to the process. In park IV, I discuss the supposed failures in the control system of administrative duties. In conclusion, I summarize the research key points, offer some suggestions to improve the environmental licensing process and establish the distinction between inefficiency and enforcement of environmental conservational legal rules. Usina Jirau is an exemplary case of how a licensing process does not slow down the Brazilian development, and it is also a calling for Brazil to modernize and rationalize its environmental regulatory framework.